Analysis of the Impact of the Covid-19 Pandemic on Financial Performance: Empirical Study of Information Technology Companies in Asean Countries - Fina Tazkiya (Kirana Publisher (KNPub), 2024)
This study aims to analyze financial performance during and after the covid-19 pandemic in information technology companies in ASEAN countries. Financial performance variables are proxied by profitability ratios using Return On Asset (ROA), liquidity ratios using Current Ratio (CR), activity ratios using Total Asset Turnover (TATO), and solvency ratios using Debt To Equity Ratio (DER). Using company financial data with a cross-country population in countries that are members of the ASEAN countries including Indonesia, Malaysia, Singapore, Philippines, and Thailand. The total number of samples used was 84 information technology companies. This research is a quantitative research with analysis method using Wilcoxon Signed Ranks Test comparative analysis. The results showed significant differences in Indonesia in CR and DER, and in Thailand in TATO. This study also shows from the five countries that Indonesia has the best financial performance because it experiences a significant average increase. compared to other countries that tend to experience an average decrease even though it is not significant. The decline can be seen in Malaysia and Thailand which experienced an average decline, while in Singapore and the Philippines although there was a decrease but there was also an increase.